Detection of IL-27 in Patients with Visceral leishmaniasis - ALfakar, Suha Abdullah Oudah; Khalil Ismail Abid Mohammed; Ameen Abdul Hasan Al-Alwany; Jinan Mousa (University of Thi-Qar Journal of Science, 2025)
Visceral leishmaniasis (VL), caused by the protozoan parasites of the Leishmania donovani complex, remains one of the most significant neglected tropical diseases. Immune response mechanisms play a critical role in both resistance and pathogenesis of VL This study included 32 VL patients (19 females, 13 males, 2 months to 5 years old) and 30 healthy controls (1 month to 11 years old). Blood samples were obtained from the Central Public Health Laboratories (CPHL). The serum was isolated by centrifuging blood samples at 1000g for 5 minutes. Human IL-27 levels were quantified using an ELISA kit (Elabscience Biotechnology Inc., USA; catalog No. E-EL-H2338) following the manufacturer’s protocol. This study found significantly higher IL-27 levels in visceral leishmaniasis patients (54.120 pg/ml) compared to the control group (28.745 pg/ml). was a significant between the median levels of IL-27 in patients and the control group, where the p IL-27 plays a significant role in the pathogenesis of visceral leishmaniasis. Its potential as a biomarker for active disease and for monitoring treatment response warrants further investigation, irrespective of the causative agent or geographic location.